The Consideration of Maslahat in the Imposition of the Death Penalty for Serious Sexual Crimes in Indonesia - Syatar, Abdul; Abubakar, Achmad; Kurniati, Kurniati; Bedong, M. Ali Rusdi; Ahmad, Ahmad (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aimed to provide efforts to strengthen the law if changes to regulations occur, which must be accompanied by academic and socio-political approaches. In Indonesia, there is a new form of sexual crime whether verbal, non-physical, physical, or online. The prevalence of such incidents reflects a troubling trend that needs urgent attention from both authorities and society. This research was field research, equipped with qualitative data. The data sources included observational research, interviews, and documentation as well as literature studies by reviewing documents relating to criminal sanctions for adultery, especially from the Criminal Code, outside the Criminal Code, and manuscripts of Islamic criminal law. The beneficial theory used was the Al-BÅ«tÄ« version, which emphasized the validity of al-â€˜uqÅ«bah al-IslÄmiyah. The research findings revealed that in the event of changes to criminal law in Indonesia, maslahat considerations are prioritized, particularly in cases of grave sexual crimes, the death penalty should be applied. The government must consider things such as benefits, cultural values, and societal perspectives when making criminal punishment policies. In Indonesia, several backgrounds supported the choice of the death penalty for sexual crimes. The expected benefits are community protection, preventative action, justice for victims, and the elimination of dangerous perpetrators in the future. The legal situation governing sexual crimes in Indonesia is increasingly pitiful, and a change is needed.